2017
DOI: 10.1038/cddis.2017.383
|View full text |Cite|
|
Sign up to set email alerts
|

BET bromodomain inhibitors synergize with ATR inhibitors in melanoma

Abstract: Metastatic malignant melanoma continues to be a challenging disease despite clinical translation of the comprehensive understanding of driver mutations and how melanoma cells evade immune attack. In Myc-driven lymphoma, efficacy of epigenetic inhibitors of the bromodomain and extra-terminal domain (BET) family of bromodomain proteins can be enhanced by combination therapy with inhibitors of the DNA damage response kinase ATR. Whether this combination is active in solid malignancies like melanoma, and how it re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…Interestingly, cellular fractionation confirmed that both the cytoplasmic and nuclear expression of p62 increased ( Figure 1 D). To determine if p62 accumulation in these esophageal cell lines occurred via the same mechanism as previously reported, OE21 cells were treated with VX-970 in the absence of any other exogenous stress and qPCR carried out for the well-characterized target of ER stress; CHOP, as well as p62 ( Muralidharan et al., 2016 , 2017 ). Surprisingly and in contrast to the previous reports, neither the level of p62 nor CHOP mRNA was significantly altered in response to exposure to VX-970 ( Figure 1 E).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Interestingly, cellular fractionation confirmed that both the cytoplasmic and nuclear expression of p62 increased ( Figure 1 D). To determine if p62 accumulation in these esophageal cell lines occurred via the same mechanism as previously reported, OE21 cells were treated with VX-970 in the absence of any other exogenous stress and qPCR carried out for the well-characterized target of ER stress; CHOP, as well as p62 ( Muralidharan et al., 2016 , 2017 ). Surprisingly and in contrast to the previous reports, neither the level of p62 nor CHOP mRNA was significantly altered in response to exposure to VX-970 ( Figure 1 E).…”
Section: Resultsmentioning
confidence: 90%
“…However, the reported induction of p62 observed in response to the ATR inhibitor, VE-821, was not linked to a blockage in autophagy as another commonly used marker of autophagy, light chain 3 (LC3), appeared unaffected ( Muralidharan et al., 2016 ). In a follow-on study focused on melanoma, inhibition of ATR was again demonstrated to lead to the induction of SASP/ER stress, which included an accumulation of p62 and the transcription factor C/EBP homologous protein (CHOP) ( Muralidharan et al., 2017 ). The accumulation of p62 has also been implicated in compromising DNA repair, genomic integrity, and in accelerated aging ( Eliopoulos et al., 2016 ; Hewitt et al., 2016 ; Kang et al., 2015 ; Kwon et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several papers also have reported that BET inhibitors synergize with cell cycle checkpoint modulators, such as CDK inhibitors or ATR inhibitors . Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several papers also have reported that BET inhibitors synergize with cell cycle checkpoint modulators, such as CDK inhibitors 42 or ATR inhibitors. 31,43 Zhang et al 43 reported that BRD4 inhibitor synergized with an ATR inhibitor through reducing the phosphorylation of CHK1. CHK1 inhibitors would also synergize with BET inhibitors theoretically, as CHK1 inhibitors could drive mitotic entry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation